Managing COPD - Russell, Richard; Ford, Paul A.; Barnes, Peter J. 1946-; Peter Barnes (Springer, 2011)
Managing COPD is an in-depth guide on the management of patients with COPD concentrating on the impact of COPD on a patient as well as how healthcare professionals can intervene and educate the patient at an early stage and thereby slow the onset of severe symptoms. This book has been designed to increase physician awareness of the pathological processes involved in the aetiology of COPD which underpins effective disease management.